2014
DOI: 10.1155/2014/816979
|View full text |Cite
|
Sign up to set email alerts
|

Immobilized Lentivirus Vector on Chondroitin Sulfate-Hyaluronate Acid-Silk Fibroin Hybrid Scaffold for Tissue-Engineered Ligament-Bone Junction

Abstract: The lack of a fibrocartilage layer between graft and bone remains the leading cause of graft failure after anterior cruciate ligament (ACL) reconstruction. The objective of this study was to develop a gene-modified silk cable-reinforced chondroitin sulfate-hyaluronate acid-silk fibroin (CHS) hybrid scaffold for reconstructing the fibrocartilage layer. The scaffold was fabricated by lyophilizing the CHS mixture with braided silk cables. The scanning electronic microscopy (SEM) showed that microporous CHS sponge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 33 publications
1
20
0
1
Order By: Relevance
“…Sun et al[161] coupled a TGF-β3-expressing lentiviral vector to a silk scaffold reinforced with chondroitin sulfate for the fabrication of an interface-like construct. MSCs were cultured on the scaffold and continuously transfected with the coupled lentivirus.…”
mentioning
confidence: 99%
“…Sun et al[161] coupled a TGF-β3-expressing lentiviral vector to a silk scaffold reinforced with chondroitin sulfate for the fabrication of an interface-like construct. MSCs were cultured on the scaffold and continuously transfected with the coupled lentivirus.…”
mentioning
confidence: 99%
“…Sun et al fabricated a gene-modified scaffold by lyophilizing the CHS mixture with braided silk cables for fibrocartilage application [87]. The scaffold, seeded with mesenchymal stem cells (MSCs), showed vigorous cell proliferation and differentiation to reconstruct the cartilage.…”
Section: Tissue Engineering Applications Of Braided Scaffoldsmentioning
confidence: 99%
“…76 For engineering of the interface between tendon and bone, immobilization of a TGF- β3 expressing lentiviral vector onto a scaffold induced a chondrogenic phenotype by mesenchymal stem cells. 77 Not all studies to evaluate the efficacy of growth factors are as successful when applied to animal models as in vitro studies would suggest. For example, adipose stem cells transduced with BMP-2 and seeded onto aligned PLGA scaffolds in an attempt to improve tendon-bone healing had reduced trabecular bone at the tendon-bone interface and reduced mechanical properties compared to scaffolds not producing BMP-2 in a rat model, therefore use of BMP-2 for enhanced tendon-bone repair at the rotator cuff was not recommended; these results were consistent with several similar studies previously reported, but also in contrast to other studies suggesting a positive effect of BMP-2 in tendon-bone or ligament-bone healing.…”
Section: Cells and Differentiation Pathwaysmentioning
confidence: 99%